REKONSTRUKSI SEJARAH SHALAT SEBAGAI LEMBAGA KEAGAMAAN ISLAM (Telaah kitab Tafsir Ibnu Katsir) - Oktari Kanus (Universitas Islam Negeri Imam Bonjol Padang, 2019)
This research was conducted in order to reveal the details and details of the history of prayer history in the interpretation of Ibn Kathir. In this study, several important conclusions can be taken, First, prayer actually has been long before Islam came, as evidenced by the practices of prayer performed by Pagan around the Ka'bah in certain different ways and relationships with the way of Islamic prayer compilation comes. Second, from the interpretation data that the writer can convey the period of the stipulation of prayer in the interpretation of Ibn Kathir into two, namely the obligation prayer before Isra` and Mi`raj, and obliation prayer by Isra` and Mi`raj. To pray before Isra` and Mi`raj, the Messenger of Allah had performed the evening prayer through Surat al-Muzzammil sentence 1 and prayed in the morning and evening with the anatomy of the raka`at prayer only two raka`at-dua raka`at, because of Isra `and Mi`raj as the beginning of the five-day prayer period, raka`at prayer still consists of two raka`at, the prayer provisions are fourteen raka`at fix the Prophet's compilation in Medina, by providing the two prayers raka`at is given to those who is on the way (Safar) and prayer with four raka`at is intended for the settled. Third, the night prayer required to complete the beginning of prophethood became the sunna of the compilation of Muslims already in Medina, due to the factor of seeing the enthusiasm of Muslims who performed the evening prayers so that they were burdensome.